Brucellosis in Southern Israel: Comparison between Children with and without Hematological Manifestations - Fruchtman, Yariv; Leibovitz, Eugene; Berger, Aviv; Horev, Amir; Cohen, Eugen; Leibovitz, Ron; Ling, Eduard; Perry, Zvi H. (Archives of Clinical and Biomedical Research, 2020)
Objectives: We characterized the epidemiological, diagnostic and clinical aspects of children <18 years presenting with brucellosis accompanied by hematologic manifestations in Southern Israel. Method and Patients: A retrospective study on children hospitalized with brucellosis and diagnosed clinically, as well as by positive blood cultures. Patients with hematologic involvement were compared with patients w/o hematologic involvement. Results: 128/252 (50.8%) children were diagnosed with brucellosis and had blood cultures positive for Brucella melitensis. Thirty-three (25.8%) had hematologic manifestations (leukopenia 32, thrombocytopenia 14, 13 both). In univariate analysis, more males were diagnosed with hematologic involvement while no differences were seen between the 2 groups in known risk factors for brucellosis like use of non-pasteurized milk, contact with livestock, brucellosis among family members, clinical signs/ symptoms and presence of negative serological tests. The most common presentations in patients with hematologic manifestations were monoarthritis, lymphadenopathy and hepatomegaly (36.7%, 17.2% and 12.5%, respectively) w/o any differences compared with patients w/o hematologic manifestations. Impaired liver function tests and recurrent disease were more frequent in patients w/o hematologic involvement vs. patients with hematologic involvement (42.5% vs. 9.2%, P=0.005 and 10.4% vs. 0%, P=0.06). High antibodies titers (1:640-1:1280) were more common in patients w/o hematologic involvement (28.4% vs. 6%, P=0.002). In 3 different multivariate statistical models, patients with hematologic manifestations were older than those w/o hematologic manifestations. Conclusions: Brucellosis accompanied by hematologic manifestations is common in children in Southern Israel. Patients with hematological involvement did n